Intracranial Carotid Arteriosclerosis Mediates the Association Between Blood Pressure and Cerebral Small Vessel Disease. Issue 3 (2nd December 2022) - Melgarejo, Jesus D.; Vernooij, Meike W.; Ikram, M. Arfan; Zhang, Zhen-Yu; Bos, Daniel
Abstract : Background: Intracranial arteriosclerosis could explain the association between blood pressure (BP) and cerebral small vessel disease (CSVD). Therefore, we tested whether intracranial carotid artery calcification (ICAC) mediates the association between BP and CSVD and determined pathophysiological mechanisms based on ICAC subtypes. Methods: One thousand four hundred fifty-eight stroke-free participants from the Rotterdam Study (mean age, 68 years; 52% women) underwent nonenhanced computed tomography scans to quantify ICAC volume (mm 3 ) between 2003 and 2015. ICAC was categorized into intimal and internal elastic lamina calcifications. CSVD included white matter hyperintensities volume, the presence of lacunes, and cerebral microbleeds visualized on magnetic resonance imaging. Office BP included systolic BP, diastolic BP, pulse pressure, and mean arterial pressure. Mediation analysis included a 2-way decomposition to determine the direct association between BP and CSVD and the indirect or mediated effect (negative or positive mediations expressed in %) of log-ICAC volume on such association. Results: BP and log-ICAC were correlated and were also associated with CSVD. In all participants, total log-ICAC volume mediated the association of diastolic BP (−14.5%) and pulse pressure (16.5%) with log-white matter hyperintensities. Internal elastic lamina log-ICAC volume mediated −19.5% of the association between diastolic BP and log-white matter hyperintensities; intimal log-ICAC volume did not mediate associations. For lacunes, total and internal elastic lamina log-ICAC volume mediated the association of diastolic BP (−40% and −45.8%) and pulse pressure (26.9% and 18.2%). We did not observe mediations for cerebral microbleeds. Conclusions: Intracranial arteriosclerosis mediates the association between BP and CSVD. Internal elastic lamina calcification, considered a proxy of arterial stiffness, is the leading mechanism explaining the link between BP and CSVD.